فعالية استخدام المواد التعليمية على أساس الدراسة التقابلية في تعليم مهارة الكتابة بقسم تعليم اللغة العربية جامعة مولانا مالك إبراهيم الإسلامية الحكومية مالانج - Aminata, Diah Dina (UIN Maulana Malik Ibrahim Malang, 2020)
Most of university students use Indonesian language structure in Arabic language writing. So, those sentences become false. The university student just obey to the lesson book that used in learning process as the common, whereas that lesson book still doesn’t pay attention of the differences and the similar from the structure of the main languages and the language that they are studied. Contrastive analysis is an activity to find both of the differences and similar of two languages and also as the solution of the languages’ problem. So, the researcher want to know the effectivity of the lesson book of writing skill by using contrastive analysis theory in Arabic teaching department of State Islamic University of Maulana Malik Ibrahim Malang.Based on that thinking, this research’s purposes are to know about The effectivity of lesson book on writing skill by using Contrastive Analysis .This research uses quantitative approach. And this research’s kind of method is experiment model. For the analysis of this research’s data, are used inferential statistic analysis by using t test.The results of this research is The researcher use test of two chapters using from the teaching material with intact group comparison method, that is by dividing the class become two groups, control group and experiment group. In the test of the first chapter, the score is 26,6 (t-arithmetic) 1,27 (t-table), it means that this teaching material is effective. In the test of the second chapter, the researcher gets the score 16,5 (t-arithmetic) 1,27 (t-table), it means that this this teaching material is effective.